2001
DOI: 10.1046/j.1365-2710.2001.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

A leucine(7)-to-proline(7) polymorphism in the signal peptide of neuropeptide Y was not identified in the Japanese population

Abstract: The incidence of the Leu(7)-to-Pro(7) polymorphism in the signal peptide of NPY was extremely low in Japanese people, suggesting that the polymorphism producing Pro(7) is not one of the genetic determinant factors affecting serum cholesterol levels in Japanese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…15,25,26 Irreproducibility of positive findings has been a common criticism levelled at association studies investigating the common genetic basis of complex diseases. 22 The frequency of the Pro7 allele has been reported to be 0.08 in Finns, 0.03 in Dutchmen 17 and virtually absent in Japanese 28,29 and Koreans. 30 An extremely low frequency of Pro7 was observed in a Chinese population, 31 whereas Duan et al 32 failed to detect this allele in the same region.…”
Section: Discussionmentioning
confidence: 99%
“…15,25,26 Irreproducibility of positive findings has been a common criticism levelled at association studies investigating the common genetic basis of complex diseases. 22 The frequency of the Pro7 allele has been reported to be 0.08 in Finns, 0.03 in Dutchmen 17 and virtually absent in Japanese 28,29 and Koreans. 30 An extremely low frequency of Pro7 was observed in a Chinese population, 31 whereas Duan et al 32 failed to detect this allele in the same region.…”
Section: Discussionmentioning
confidence: 99%
“…The Pro7 allele has already been found in a few populations worldwide, such as Asians [Japanese (Drube et al 2001;Makino et al 2001;Okubo et al 2001;Lappalainen et al 2002;Itokawa et al 2003); Koreans (Ding et al 2002); Japanese in Tokyo and Han, Chinese in Beijing (http://www.hapmap.org)] and Africans [African-American (Lappalainen et al 2002); Yoruba in Ibadan, Nigeria (http://www.hapmap.org)]. Jia et al (2005) reported an extremely low frequency of Pro7 in a Chinese population, although Duan et al (2005) failed to detect this allele in the same region.…”
Section: Discussionmentioning
confidence: 99%
“…There was no report of the presence of this allele among Japanese (Drube et al 2001;Makino et al 2001;Itokawa et al 2003) and Korean populations (Ding et al 2002). Jia et al (2005) reported an extremely low frequency of the Pro7 allele in China.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the frequency of the Leu 7 -to-Pro 7 polymorphism appeared to vary from one population to the other, since the incidence in healthy Japanese was extremely low. It is therefore unlikely that NPY represents a strong genetic factor affecting cholesterol among Japanese people [139]. The exact NPY-mediated mechanisms influencing blood lipid concentrations and deposition in the vasculature are unknown.…”
Section: Cardiovascular Regulationmentioning
confidence: 99%